Everyday tasks impair spatiotemporal variables of gait in older adults with Parkinson's disease - Yamada, Patrícia de Aguiar [UNESP]; Amaral-Felipe, Késia Maísa [UNESP]; Spinoso, Deborah Hebling [UNESP]; Abreu, Daniela Cristina Carvalho de; Stroppa-Marques, Ana Elisa Zuliani [UNESP]; Faganello-Navega, Flávia Roberta [UNESP] (Elsevier, 2020)
Introduction: Although it is known that individuals with Parkinson's disease (PD) have difficulties performing dual-task activities, most of the studies have verified the effect of dual tasks on gait using tasks that are uncommon to perform while walking. However, the realization of tasks involving gait that really represents the daily activities carried out by the participants, allow us to detect real fall risk situations of individuals with PD during their gait. Objective: Our aim was to verify the influence of daily-life dual-tasks on gait spatiotemporal variables of the older adults with PD. Methods: 20 older adults without PD and 20 older adults with PD participated in the study. Gait kinematic was analyzed under three different conditions: walking without dual task, walking carrying bags with weight, and walking talking on the cell phone. Results: Older adults with PD presented lower speed (p = . 001), cadence (p = . 039), and shorter step length (p = . 028) than older adults without PD during walking without dual tasks. When walking while carrying bags with weight, older adults with PD had a lower speed (p <. 001), cadence (p = . 015), shorter step length (p = . 008), and greater double support time (p = . 021) compared with older adults without PD. During walking while talking on the cell phone, older adults with PD walked with lower speed (p <. 001), cadence (p = . 013), shorter step length (p = . 001) and swing time (p = . 013), and increased double support time (p = . 008) and support time (p = . 014) in relation to older adults without PD. Conclusion: Daily-life dual tasks impair the spatiotemporal variables of gait in the older adults with PD, which was most evident during walking talking on the cell phone.
Keywords: Dual task; Everyday activities; Gait; Kinematic; Parkinson's disease